Análisis de la región de formación estelar vinculada a la fuente IRAS 15492-5426 - Corvera, Andrea V. (2021)
A study was conducted on the star formation region linked to the IRAS source 15492-546 located in the complex G327.3-0.5. This one consists of a dark molecular cloud in which the emission of their molecules has been studied using spectral bands on radio and IR. In this work we present the study of the ionized hydrogen region (RH II) RCW 97 located at the edge of the complex. For this, images of 21 cm H I spectral line emission from the Southern Galactic Plane Survey (SGPS) and images of continuum from the Sydney University Molonglo Sky Survey (SUMSS), were analyzed. With the first kind of data we were able to investigate the radial velocity of the H II region, with it and models for the galactic rotation we could find its kinematic distance. Parameters such as bright temperature, {electronic density and mass were also estimated. With the data of the second survey} we measured the flux density of RCW97 in 843 MHz which along with values of flux density from the other frequencies allowed us to know the spectral index and the frequency at which this region would be optically thin. We investigated what spectral characteristics the stars that form in the complex should have to generate the H II region, calculating the excitation parameter of the H II region.